Yield, Carcass and Sensory Characteristics of Broiler Meat after Withdrawal of Anticoccidial Semduramicin from Feed - Islam, K.M.S.; Schumacher, A.; Gropp, J.M.; Schoon, H.-A. (Pakistan Journal of Nutrition, 2007)
With (25 mg kg -1 feed) or without semduramicin (coccidiostat) containing feeds were offered for 35 days to 160 (2 treatmentsX10 replicatesX8 birds/replicate) newly hatched female broiler chicks to know the effect of semduramicin on growth performance as well as carcass and sensory characteristics of meat after 5 to 8 days withdrawal of semduramicin. Diets were offered to the birds formulated based on soybean meal, corn and soybean oil. Blood parameters, enzyme profiles and health status were studied from selected birds at the end of the growth trial. Twenty birds (2 per replicate) of each feeding groups were transferred into floor pens and offered only the control diet. Five broilers from each feeding group (control and withdrawal) were slaughtered at day 5, 6, 7 and 8. Body weight (and feed conversion efficiency-FCE; g gain kg -1 feed) after 35 days feeding trial was 2,062 (665) and 2,084 (678) for the control and semduramicin group (p>0.05), respectively. Feed intake (3,018 vs 2,996 g) was also similar (p>0.05) in both groups. Blood parameters, enzyme profiles and pathological study did not give evidence for any adverse influence of semduramicin. The semduramicin group had slightly higher body weight (2,569 vs. 2,477 g; P>0.05) at slaughter after 5-8 days withdrawal. Nevertheless, there were no treatment effects (P>0.05) on hot carcass weight, viscera (g or percent of bw), dressing percentage, edible portions (breast muscles, haunch), fat and skin portions. Also the sensory characteristics (juiciness, tenderness, aroma, general impression) were not influenced by the treatment. However, the aroma/flavour of carcass in the semduramicin group was improved (P< 0.05), probably due to a slightly higher intramuscularly fat content in meat (P< 0.05).